An alternative media and technique in batik for primary school / Azmi Abdullah - Abdullah, Azmi (2013)
Batik is a craft that was introduced in primary schools in Malaysia. Visual arts education is a medium for batik craft in primary school. This study focuses on the problem of teachers conducting batik activities in primary schools. Problems arise when teachers lose interest in batik activities in primary schools. Survey questions has been made that teachers lose interest because of the use of hot wax on batik activities. In this study, the researchers explore the literature review to find alternative media on batik activities in primary schools. This research conducted experiments method and art base research to explore solution. Statistical data and art base research combined incorporated into this study. Experimental with an alternative media on batik technique will be made. Purpose of this research is to find an alternative and technique in batik for primary school